Experimental studies on seismic behaviour of RC columns under different loading directions - Erianto (2011)
Non-ductile RC columns are common in old building, these columns built before significant advancements in building code provisions for reinforced concrete were instituted in the mid 1970s. The idea of using irregular shaped columns such as L-shaped columns at the corners of frame structures and at enclosure of elevator shafts have been extensively used in old building, especially in Singapore. However, not much study has been published regarding the seismic behavior of L-shaped columns. Therefore this study involving non-ductile RC columns with L-shaped sections are carried out to investigate the seismic performance of such columns under different directions of cyclic loading.